PROGRAM PEMBERDAYAAN KOMUNITAS ADAT TERPENCIL (KAT) OLEH DINAS SOSIAL KABUPATEN BENGKALIS TERHADAP SUKU SAKAI DI DESA SEMUNAI KECAMATAN PINGGIR TAHUN 2016-2018 - Renaldi "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The 1945 Constitution of the Republic of Indonesia states that the Republic of Indonesia is a unitary state in the form of a republic. The granting of the widest possible autonomy to the Regions is directed to accelerate the realization of the welfare of the community through improved services, empowerment, and community participation. In addition, through broad autonomy, in the strategic environment of globalization, the Region is expected to be able to increase its competitiveness by paying attention to the principles of democracy, equity, justice, privileges and specificities as well as the potential and diversity of the Region in the Unitary State of the Republic of Indonesia.This study aims to describe the empowerment program of remote indigenous communities by the Bengkalis Regency Social Service towards the Sakai Tribe in Semunai Village, Pinggir Subdistrict and to determine the factors that hamper the Bengkalis Regency Social Service towards the remote indigenous community empowerment program (KAT). This research uses descriptive qualitative methods and data collection techniques by observation, literature study and interviews.The results of this study can be seen that the implementation of the aid program by the Bengkalis Regency Social Service towards KAT in the form of assistance for livable houses (RLH), rainwater collection assistance (PAH) and school equipment assistance. The empowerment program carried out by Bengkalis Regency Social Service has not been implemented optimally and only covers physical aspects. This can be seen in the implementation of the empowerment program that is uneven and unrealized with the target to be achieved. The inhibiting factor in the implementation of remote indigenous community empowerment programs is the lack of budget in implementing remote indigenous community empowerment programs, the culture of remote indigenous communities that are still primitive and dependent (Dependency). Keywords: Regional Autonomy, Social Empowerment, Empowerment Preparation